A Study of the Complexities, Challenges, and Business Opportunities Available Within the Nigerian Aircraft Maintenance, Repair, and Overhaul Sector - Benjamin Hebron, Tuti (Digital Repository of Theses, 2026)
This research examines the complexities, challenges, and business opportunities within Nigeria's aviation maintenance, repair, and overhaul (MRO) sector. It seeks to investigate the key systemic vulnerabilities that hinder the development of a safe, efficient, and resilient aviation MRO sector in Nigeria, despite the sector's rich history and government investments over the years. To accomplish this project, we used a multi-part approach, integrating quantitative data from surveys of 205 stakeholders. This data was collated using a structured questionnaire administered via Google Forms, with qualitative insights derived from thematic analysis and an extensive review of global and African MRO case studies. The study is guided by three principal questions: the sector's inherent complexities, the primary challenges to productivity and development, and the business opportunities available for indigenous MRO for enthusiasts and would-be investors alike. Several statistical analysis tools were used to provide more practical insights. These include Multiple Linear Regression, which revealed a highly significant model (p < .001), indicating that strategic drivers, namely, government policy support, stakeholder collaboration, and investment in specialised training, are significant predictors of a positive economic outlook for the sector. The Chi-Square test of independence (p = 0.239) further indicates that regulatory hurdles are perceived as a consistent systemic barrier across all experience levels. Empirical findings also identify component repair (86.8%) and training services (87.3%) as the most viable immediate business opportunities for indigenous enterprises. The research concludes by presenting a data-driven roadmap for investors and policymakers, offering actionable recommendations that can directly influence policy development and guide strategic investment decisions to address challenges in Nigeria's MRO sector.